New Social Groups as the Factor of Political Instability in the Modern Society - A. A. Soldatov (Дискурс, 2021)
Introduction. The basic reasons of increasing turbulence in the political sphere of different state entities are analyzed. It is emphasized that the main fault of this phenomenon was the active formation of the new social groups.Methodology and sources. A sociological analysis of stratification models of society, starting from the 19th century and up to our days in the context of the works of K. Marx, M. Weber, R. Florida, G. Stending, I. Vallerstein and others is used.Results and discussion. The conclusion is made that the political sphere itself is self-sufficient, political groupings play an independent and very important role, and new tendencies of the modern global market significantly change of the society.As new social groups are formed different factors of growth emerge which include functional flexibility and lack of guarantee of the working place. It can also asserted that technological progress at the present stage doesn’t recognize civilizational boundaries and ignores the factor of backwardness of some countries and regions which leads to ambiguous results and can cause social cataclysms.Conclusion. A number of important conclusions follow from these circumstances. Among the active participants and actious of participants there are no clear of stratification barriers. Financial indicators still play a role. Indicators of financial position, level of education, and professional classification in combination with other factor still play a role. Blurred social boundaries inevitably imply the absence of a solid ideological base, which is replaced by protest trends often unrelated to political events and demands. The actions of the green eco-activists or LGBT community can serve as an example. The problem is that the political individuals react actively to any movement, which make the sphere of political decisions lose its authentic character.